Perbandingan Performansi Single Web Server Dan Multi Web Server Dengan Uji Coba Paired Sample T Test - Molavi Arman (ISB Atma Luhur, 2019)
Abstract— The more the development of the era then the more advanced technology, where this technology is very helpful human in carrying out daily activities, in connection with it with the development of technology a person can use an internet, which the internet is very helpful to the user in obtaining information and can also be used as communication media. the web can also be said as a medium that is used as to access information through the internet, if more and more internet users to access the web it will cause the slow performance of the web server. Therefore in this paper the authors make a study on Comparison Performance Single Web Server And Multi Web Server With Different Test Using Paired Sample T Test. To see the performance between single and multi web server can be seen in terms of components Throughput, Response Time, CPU Utilization by using httpref application then to see test different between single web server and multi web server by using paired sample t test. The application of paired sample t test to see the difference test using the predefined hypothesis which to support the decision can be seen that the sig value obtained between the single server web server test and the multi server web server is 0,000 and the value is below 0.05, then based on the hypothesis it can be concluded that between single web server and multi web server there is significant difference from the test result..Keywords: Performansi, Server, Httperf, Web, Paired sample t test